PERTANGGUNGJAWABAN TINDAK PIDANA PENGGELAPAN DALAM JABATAN PADA PERSEROAN TERBATAS (PT) KARYA TRANPORTASI ABADI(Studi Putusan Nomor : 137/Pid.B/2023/PN Kla) - Shalsha Berliana; Lintje Anna Marpaung (INTELIGENSIA MEDIA, 2024)
A crime is an act or deed of a person that violates criminal law. Violations that are often committed in an agency usually refer to embezzlement, where the criminal act of embezzlement is an action that is directly related to a person's morals which is carried out intentionally and is against the law. ownership of an item that is the property of another person within his or her control. The criminal act of embezzlement in office is included in Article 374 of the Criminal Code, this is because the person who commits this act aims to benefit himself, namely by abusing the authority he has, with the object being goods or property belonging to another person. The problem of this research is the factors that cause perpetrators to commit criminal acts of embezzlement in office at PT Karya Tranportasi Abadi as well as what criminal responsibility there is for perpetrators of embezzlement in office at PT Karya Tranportasi Abadi. This research method uses a normative and empirical juridical approach. The sources and types of data used are primary and secondary data. Data collection through library research (Library Research) and field research (Field Research). Data processing is carried out by selecting and checking the data obtained for its completeness, as well as classifying or grouping the data systematically. The data analysis used is qualitative juridical. The results of this research can be concluded that there are two main factors that cause the crime of embezzlement in office in a limited liability company, namely economic factors and opportunity factors, the perpetrator feels pressured by the needs and desires of his wife and then gets the opportunity because he has more power so this action occurs. Then for criminal responsibility in this case the judge decided to sentence the defendant to prison for one year and three months as stated in Decision Number 137/Pid.B/2023/PN Kla.